Enterococcus spp. from chicken meat collected 20 years apart overcome multiple stresses occurring in the poultry production chain: Antibiotics, copper and acids - Rebelo, Andreia (2023)
Poultry meat has been a vehicle of antibiotic resistant bacteria and genes. Yet, the diversity of selective pressures associated with their maintenance in the poultry-production chain remains poorly explored. We evaluated the susceptibility of Enterococcus spp. from chicken meat collected 20 years apart to antibiotics, metals, acidic pH and peracetic acid-PAA. Contemporary chicken-meat samples (n = 53 batches, each including a pool of neck skin from 10 single carcasses) were collected in a slaughterhouse facility using PAA as disinfectant (March–August 2018, North of Portugal). Broilers were raised in intensive farms (n = 29) using CuSO4 and organic acids as feed additives. Data were compared with that of 67 samples recovered in the same region during 1999–2001. All 2018 samples had multidrug resistant-MDR isolates, with >45 % carrying Enterococcus faecalis, Enterococcus faecium or Enterococcus gallinarum resistant to tetracycline, erythromycin, ampicillin, quinupristin-dalfopristin, ciprofloxacin, chloramphenicol or aminoglycosides. Resistance rates were similar (P > 0.05) to those of 1999–2001 samples for all but five antibiotics. The decrease of samples carrying vancomycin-resistant isolates from 46 % to 0 % between 1999-2001 and 2018 was the most striking difference. Isolates from both periods were similarly susceptible to acid pH [minimum-growth pH (4.5-5.0), minimum-survival pH (3.0-4.0)] and to PAA (MIC90 = 100–120 mg/L/MBC90 = 140–160 mg/L; below concentrations used in slaughterhouse). Copper tolerance genes (tcrB and/or cueO) were respectively detected in 21 % and 4 % of 2018 and 1999-2001 samples. The tcrB gene was only detected in E. faecalis (MICCuSO4 > 12 mM), and their genomes were compared with other international ones of chicken origin (PATRIC database), revealing a polyclonal population and a plasmid or chromosomal location for tcrB. The tcrB plasmids shared diverse genetic modules, including multiple antimicrobial resistance genes (e.g. to tetracyclines, chloramphenicol, macrolide-lincosamide-streptogramin B-MLSB, aminoglycosides, bacitracin, coccidiostats). When in chromosome, the tcrB gene was co-located closely to merA (mercury) genes. Chicken meat remains an important vehicle of MDR Enterococcus spp. able to survive under diverse stresses (e.g. copper, acid) potentially contributing to these bacteria maintenance and flux among animal-environment-humans.